Phylogenetic relationships and taxonomic position of genus Hyperacrius (Rodentia: Arvicolinae) from Kashmir based on evidences from analysis of mitochondrial genome and study of skull morphology - Natalia I. Abramson; Fedor N. Golenishchev; Semen Yu. Bodrov; Olga V. Bondareva; Evgeny A. Genelt-Yanovskiy; Tatyana V. Petrova (PeerJ, 2020)
In this article, we present the nearly complete mitochondrial genome of the Subalpine Kashmir vole Hyperacrius fertilis (Arvicolinae, Cricetidae, Rodentia), assembled using data from Illumina next-generation sequencing (NGS) of the DNA from a century-old museum specimen. De novo assembly consisted of 16,341 bp and included all mitogenome protein-coding genes as well as 12S and 16S RNAs, tRNAs and D-loop. Using the alignment of protein-coding genes of 14 previously published Arvicolini tribe mitogenomes, seven Clethrionomyini mitogenomes, and also Ondatra and Dicrostonyx outgroups, we conducted phylogenetic reconstructions based on a dataset of 13 protein-coding genes (PCGs) under maximum likelihood and Bayesian inference. Phylogenetic analyses robustly supported the phylogenetic position of this species within the tribe Arvicolini. Among the Arvicolini, Hyperacrius represents one of the early-diverged lineages. This result of phylogenetic analysis altered the conventional view on phylogenetic relatedness between Hyperacrius and Alticola and prompted the revision of morphological characters underlying the former assumption. Morphological analysis performed here confirmed molecular data and provided additional evidence for taxonomic replacement of the genus Hyperacrius from the tribe Clethrionomyini to the tribe Arvicolini.